Meningkatkan Student Engagement dan Hasil Belajar Menggunakan Media Pembelajaran Pemrograman Berbasis Game - Noven Indra Prasetya; Shofiya Syidada (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2026)
Computer programming is an essential skill in the digital era, yet many students struggle due to teacher-centered lecture methods that rely heavily on one-way explanations and passive notetaking. This study aims to develop a game-based programming learning media to enhance student engagement and learning outcomes. Using Design-based Research (DBR) with the ADDIE model, a web-based media integrating game elements such as live coding, leaderboards, and level-based challenges was designed and tested. Participants included 276 students from Wijaya Kusuma Surabaya University, selected via purposive sampling. Data were collected through knowledge tests, engagement questionnaires, and user satisfaction surveys, then analyzed using descriptive statistics and paired sample t-tests. Results indicated significant improvements in student engagement (89% of students achieved high engagement) and learning outcomes (average score increase of 19.94 points). These findings demonstrate the effectiveness of game-based media in creating interactive and enjoyable learning experiences. The study contributes to the development of innovative educational methods in technology-based learning.